ARGILA DISPERSA EM ÁGUA EM LATOSSOLOS APÓS LONGO TEMPO DE PLANTIO DIRETO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2017)
The water dispersible clay study contributes to monitoring possible improvements or deteriorations in soilstructure. This work aimed to evaluate water dispersible clay in Oxissols after a long time no tillage. The experiment was carried out at "Capão da Onça" School Farm, belonging to State University of Ponta Grossa-UEPG. A toposequence was identified in the area, and divided into three parts: upper third (UT), middle third (MT) Lower third (LT). In each toposequence, three systematic sampling was carried out, with a regular mesh of 5x4 m implantation, with 20 demarcated points, a meter distanced each other. The soil samples were collected with a metal cylinderin the superficial layer (0,00-0,05 m). The indicators of soil structural stability, readily dispersible clay (RDC), mechanically dispersed clay (MDC) and water dispersible clay (WDC) were determined. For RDC determination, the turbidimetry method was used. For MDC determination, the same procedure was followed for RDC, however, a longer sample shaking time was used. The WDC determination used the similar methodology for granulometric analysis determination, without chemical dispersant use. The RDC, MDC and WDC levels were correlated with physical and chemical soil attributes. The RDC showed correlation with clay, sand, P, K+, Ca2+ and Mg2+. MDC showed correlation with clay, sand, K+ and Mg2+, while WDC showed correlation only with Ca2+. The third toposequence components presented almost in RDC levels, and there was no difference between them. In these areas, when there is a brief increase in energy inputs, it was observed that the dispersion was approximately two or three times higher, when RDC and MDC levels are compared. However, MDC levels didn‟t differ in the proportions in the samples. When soil samples were subjected to high energy inputs, as in WDC case, the dispersion increased approximately fifteen times. These results suggest that, under field conditions, dispersion clay in these soil samples maybe primarily due to the effect external mechanical forces. It was concluded that these soils presented low clay dispersion. However, the dispersion can increase significantly if they are subjected to high energy inputs, for example the intense machine‟s traffic.
DISPERSIBLE CLAY IN OXISSOLS AFTER A LONG TIME OF NO TILLAGE
Keywords: agregados; dispersão; estrutura; aggregates; dispersion; structure; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA